2016
DOI: 10.3945/ajcn.116.131896
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, crossover, head-to-head comparison of eicosapentaenoic acid and docosahexaenoic acid supplementation to reduce inflammation markers in men and women: the Comparing EPA to DHA (ComparED) Study

Abstract: DHA is more effective than EPA in modulating specific markers of inflammation as well as blood lipids. Additional studies are needed to determine the effect of a long-term DHA supplementation per se on cardiovascular disease risk. This trial was registered at clinicaltrials.gov as NCT01810003.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
161
4
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(194 citation statements)
references
References 33 publications
11
161
4
10
Order By: Relevance
“…A marked increase in the n-6/n-3 ratio is associated with lipogenesis, overweight lipid oxidation and secretion, and therefore promotion of NAFLD [11]; fish oil intake varies in its hepatic fatty acid composition in supplements with n-3 PUFA, and a reduction in the n-6/n-3 ratio has already been revealed in another study [7]. Other reports demonstrated that DHA supplementation led to a greater reduction in specific makers of inflammation than that by an equal dose of EPA [17], but supplementation with varying ratios of EPA/DHA influenced different metabolic syndrome markers [15] and enhanced the positive effects of biomarkers of inflammation [12]. Accordingly, in the present study, we concentrated on the effects of various ratios of DHA/EPA (with an n-6/n-3 ratio of 4:1) on liver damage in C57BL/6 J mice with high-fat diet-induced obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A marked increase in the n-6/n-3 ratio is associated with lipogenesis, overweight lipid oxidation and secretion, and therefore promotion of NAFLD [11]; fish oil intake varies in its hepatic fatty acid composition in supplements with n-3 PUFA, and a reduction in the n-6/n-3 ratio has already been revealed in another study [7]. Other reports demonstrated that DHA supplementation led to a greater reduction in specific makers of inflammation than that by an equal dose of EPA [17], but supplementation with varying ratios of EPA/DHA influenced different metabolic syndrome markers [15] and enhanced the positive effects of biomarkers of inflammation [12]. Accordingly, in the present study, we concentrated on the effects of various ratios of DHA/EPA (with an n-6/n-3 ratio of 4:1) on liver damage in C57BL/6 J mice with high-fat diet-induced obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our research group has previously reported that DHA and EPA from fish and algal oils are more beneficial than plant oils enriched in α-linolenic acid (C18:3 n-3, ALA) at delaying atherosclerosis progression in model apoE −/− mice; an intervention with higher DHA/EPA ratios was found to be beneficial for reducing high cholesterol concentrations in the blood [16]. Nevertheless, DHA and EPA differ in their physiological functions, and a new study indicated that DHA supplementation leads to a greater reduction in specific markers of inflammation than that by an equal dose of EPA [17]. In view of these observations, it remains unclear whether DHA is more effective than DHA/EPA, there is an optimal ratio of DHA and EPA supplementation for reduction of high-fat diet-induced liver damage, and regularizing the ratio of DHA and EPA has differential effects on various symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The indication of diet supplementation in sport activities is due to the anti-inflammatory and/or antioxidant effect and consequently its action on all the processes of tissue restoration and adaptation to the physical stress and training, from the connective tissue to the neural development [4]. However, it has been shown that DHA is more effective than EPA in modulating specific markers of inflammation as well as blood lipids [5]. The epidemiological studies related to the impact of the supplementation on the physical activities are focused on supposed actions of the n-3 FA on muscle metabolism and tissue recovery [6], functional performance, and inflammation [7] and, with a very specified indications on sport, as exercise induced asthma [8], traumatic brain injury [9] or injury recovery, training adaptation, and sarcopenia [10].…”
Section: Introductionmentioning
confidence: 99%
“…The first results from the Comparing EPA to DHA Study were published recently and demonstrated for the first time, to our knowledge, that DHA is more effective than EPA in modulating specific markers of inflammation, as well as blood lipids (a greater reduction in TGs and a greater increase in HDL cholesterol) (9). Studies have shown that DHA supplementation in the maternal diet may have a favorable impact on the development of the infant's immune system and the risk of allergic or atopic diseases early in life (10).…”
Section: Recent Researchmentioning
confidence: 99%